Psychological and social factors influencing mother–child bonding in the first year after birth: a model for promoting infant and maternal well-being - La Rosa, Valentina Lucia; Alparone, Dario; Commodari, Elena (Frontiers in Psychology, 2025)
IntroductionThis study aimed to examine how maternal mental health, sleep quality, and social support influence mother-infant bonding during the first year after childbirth.MethodsA total of 1,495 mothers participated by completing standardized questionnaires that assessed the quality of bonding with their infants, experiences of childbirth-related post-traumatic stress, symptoms of postpartum depression, sleep disturbances, and levels of social support.ResultsThe results indicated that 49.6% of mothers experienced childbirth-related post-traumatic stress, 32.2% reported symptoms of postpartum depression, and 50.7% experienced sleep disturbances. Regression analysis showed that postpartum depression, poor sleep quality, older maternal age, emergency cesarean delivery, and low levels of social and partner support hurt the quality of the mother-infant bond. Depressive symptoms emerged as the strongest negative predictor, whereas adequate social and partner support positively influenced bonding.DiscussionThese findings highlight the need for early screening and interventions aimed at improving maternal mental health and social support to promote positive mother-infant bonding and healthy child development.